KUALITAS DAGING AYAM TIREN DAN AYAM SEGAR BROILER DITINJAU DARI KADAR AIR DAN LEMAK - Koriyati, Lastiana; Marhaeniyanto, Eko; Afrila, Akhadiah (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study was to determine the chemical quality of tiren chicken and fresh meat in terms of water content and fat content. Meat samples taken are breast meat. The material used in this study was a sample of 20 weeks of Lohman Strain broiler chickens. The time of research began on May 2 to May 31, in the laboratory of Universitas Brawijaya Malang and the Muhammadiyah Malang laboratory. The experimental design used was Completely Randomized Design (CRD) with 5 treatments, namely: P1 = zero hours of death; P2 = 6 hours of P3 = 12 hours of death; P4 = 18 hours long of death; P5) = 24 hours of death with 3 replications. The results showed that the chemical quality of tiren chicken and fresh chicken meat were not significantly different (P> 0.05%) in terms of moisture content, P1= 76.12 ± 0.62%, P2=76.58 ± 1.01%, P3=78, 30 ± 2.67%, P4=78.22 ± 2.59%, P5=76.21 ± 1.15%. while giving was significantly different (P 0,05%) ditinjau dari nilai kadar air, yaitu masing masing P1 = 76,12±0,62%, P2=76,58±1,01%, P3=78,30±2,67%, P4=78,22±2,59%, P5-76,21±1,15%. sedangkan nilai kadar lemak berbeda nyata (P